Juan Fernandez : de gestalte van een vakbondsleider - Balthazar, Herman; van Heetvelde, Werner; Clauwaert, Alain (Gent: Amsab-ISG, 2021)
"Herman Balthazar ; voorwoord: Werner van Heetvelde, Alain Clauwaert"